Perancangan Sistem Informasi Kepegawaian Pada Dinas PMPTSP Kabupaten Intanjaya Berbasis Web - Setiawan Markus Linggi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In today's digital era, an efficient and well-integrated personnel information system is very important for public and private organisations. In the context of the Investment Office of the One-Stop Integrated Service (PTSP) of Intanjaya Regency, it is necessary to design a personnel information system that can improve the efficiency and effectiveness of data management. The selection of this research topic is based on the need to improve employee data management. By using the Waterfall method, it is hoped that the design of this staffing information system can produce products that are well structured and in accordance with user needs. This method follows an approach consisting of several stages, namely needs analysis, system design, implementation, testing, and maintenance. The result of this research is the design of a web-based staffing information system that integrates important features such as employee data management, honorary data management. This system will be designed in a structured and well-documented manner, in accordance with the stages in the Waterfall method. With the design of this web-based staffing information system, it is expected to provide significant benefits in managing staffing data at the Investment Office of the One-Stop Integrated Service (PTSP) of Intanjaya Regency. This system can help improve operational efficiency, minimise data input errors, and improve the accuracy of staffing information.